PEMBANGUNAN BUMI PERKEMAHAN TANPA DOKUMEN AMDAL DI KABUPATEN GARUT (STUDI PUTUSAN NOMOR 2251 K/PidSus- LH/2020): Campground Construction Without Environmental Impact Assessment (EIA) Documents in Garut District (Study of Decision Number 2251 K/PidSus-LH/2020) - Deannova Rafli Subagio; Narita Adityaningrum (Faculty of Law, Universitas Trisakti, 2024)
The construction of a campground in Garut Regency has caused legal problems, because it does not have an AMDAL document and environmental permits. The problems of this article are: whether the construction of the campground carried out by the head of DISPORA to fulfill environmental permits is in accordance with the Law on Environmental Protection and Management (UUPPLH) and what legal consequences arise from development in natural resource conservation areas without AMDAL documents. This research is a normative legal research and is descriptive in nature. The results of the research and discussion show that the AMDAL document is a legal instrument that must be made by every person in charge in a business/activity that has an important impact and violations result in the revocation of environmental permits. The conclusion of this research, namely: The construction of the campground carried out by the Head of DISPORA is not in accordance with Article 36 paragraph (1) of the UUPPLH. The Head of DISPORA Garut Regency has never made an AMDAL Document to the Environmental Agency and did not apply for an Environmental Permit to BPMPT so that the Head of DISPORA was sentenced under Article 109 jo. Article 116 paragraphs (1) and (2) of UUPPLH for non-compliance in making AMDAL documents.